Genetic identity and diversity of Nigerian cacao genebank collections verified by single nucleotide polymorphisms (SNPs): a guide to field genebank management and utilization - Olasupo, F.O.; Adewale, D.B.; Aikpokpodion, P.O.; Muyiwa, A.A.; Bhattacharjee, Ranjana; Gutiérrez, O.A.; Motamayor, J.C.; Schnell, R.J.; Ebai, S.; Zhang, D. (Springer, 2018)
Nigeria is the sixth largest cacao producer in the world. Field performance and quality of cacao hybrid families is largely dependent on the genetic integrity of parental clones obtained in field genebank collections. However, information on the impact of mislabeling on seed garden output in Nigeria is lacking. Using 63 single nucleotide polymorphism (SNP) markers, we analyzed 1457 cacao trees sampled from seven major field genebank plots in Nigeria to assess the genetic integrity in Nigerian cacao germplasm. The procedure of multilocus matching with known reference clones revealed up to 78% mislabeling in recently introduced international germplasm. A high rate of mislabeling was also revealed in the West African local selections and breeding lines, using Bayesian assignment test. The problem of mislabeling has been attributed to errors from the sources of introduction, pre-planting labeling errors, and rootstocks overtaking budded scions due to poor field management. The analysis of genetic diversity revealed a good representation of the available cacao germplasm groups in Nigerian field genebanks, indicating that the genetic base of Nigeria cacao germplasm has been significantly widened through germplasm introductions. However, only a small proportion of the available germplasm in the genebank have been utilized for variety development. This study proved the utility of SNP markers for cleaning up the genebanks and reducing offtypes; thereby providing a strong basis for improving the accuracy and efficiency in cacao genebank management and breeding, as well as for mobilizing improved varieties to cacao farmers in Nigeria.